118 Interventional coronary diagnostic procedures without planned coronary stenting: safety and radiation exposure. (17th July 2020) - Kaur, Amreen; Sharma, Harish; Townend, Jonathan; Ludman, Peter F; Doshi, Sagar N; Khan, Sohail Q; Zaphiriou, Alex; George, Sudhakar; Nadir, Adnan
Abstract : Background: Interventional coronary diagnostic procedures (ICDP) allow lesion-specific management of coronary artery disease. These include pressure wire-derived fractional flow reserve (FFR) and intracoronary imaging such as optical coherence tomography (OCT) and intravascular ultrasound (IVUS). Coronary instrumentation during these procedures may increase the risk of complications, however, there is a lack of data regarding their safety and associated radiation exposure when performed alone without planned coronary stenting in routine cardiac practice. Purpose: To evaluate the safety of ICDP techniques when performed without planned coronary intervention. Methods: Consecutive patients undergoing ICDP (FFR, IVUS or OCT without planned coronary intervention) at the University Hospital Birmingham between January 2015 and December 2018 were retrospectively identified. Demographic, clinical, procedural and outcome data were collected. Results: A total of 515 patients underwent ICDP. Amongst these patients, 78% underwent FFR alone, 17% IVUS/OCT and 5% both FFR and IVUS/OCT. Patients were predominately male (67%) with a mean age of 66 years. The indication for investigation was stable angina (53%) and acute coronary syndrome (47%). Ninety-four percent of the procedures were performed via radial access. There were two wire related coronary dissections (one requiring coronary stent and one treated with a drug-coated balloon). However, there was no periprocedural death, stroke or myocardial infarction. Mean fluoroscopy time for all ICDP procedures was 8.0 mins and mean total effective dose 6.29mSv. The addition of IVUS or OCT to FFR assessment increased the mean screening time (11.2 +/- 7 mins vs 8.1 +/- 6 mins, P = 0.0118) but did not significantly alter the mean effective dose (9.1 +/- 8 mSv vs 6.5 +/- 8 mSv, p = 0.1260). Conclusion: Interventional coronary diagnostic procedures carry a low but definite risk, over and above that associated with a diagnostic only angiogram but lower than that of coronary intervention. 2)Radiation exposure is higher than expected from computed tomography-FFR (∼3mSv) which in the future may reduce the need for ICDP. Conflict of Interest: None